Minjung Theology as a Project of Profanation: Focusing on the Minjung-Event Theory of Byung-Mu Ahn - Yongtaek Jeong (Religions, 2023)
The relationship between minjung theology and the process of social change called secularization or theoretical and practical projects based on such processes of social change is complex. It requires more detailed discussions. Therefore, this paper seeks to reinterpret minjung theology as a theological minjung project using the methodology of new-style phenomenology of religion with a theoretical basis on Italian philosopher Giorgio Agamben’s conceptions of secularization and profanation as projects with religious intentions and orientations. Through this reinterpretation, the paper demonstrates that minjung theology in relation to secularization is a unique theological project with very different goals from those of Latin American liberation theology as well as other political and situation theologies. In order to accomplish this purpose, the paper first introduces French sociologist Émile Durkheim who has explained secularization differently from German sociologist Max Weber. It then shows that secularization is not the only way in which the sacred is reappropriated through Agamben’s discussions of secularization and profanation. To identify the passage from secularization to profanation of the concept of minjung, this paper analyzes the minjung-event theory of Byung-Mu Ahn, a representative first-generation minjung theologian. This theory emphasizes the importance of “event” as a way of understanding minjung instead of defining it conceptually. Insofar as it presents the minjung as an intrinsically unnamable, invisible, and unpredictable event, a form of religious phenomenon called “the sacred”, minjung-event theory involves an attempt to secularize Jesus-Messiah as the Minjung-Messiah. In conclusion, this paper argues that beyond the secularization of the Messiah into the Minjung, minjung-event theory moves toward a dialectical project of desacralization and re-sacralization, in which the minjung itself is profaned into an event.